Profit-sharing vs Interest Rates an Analysis of The Interaction Between Sharia and Conventional Banking in Indonesia - Hilyati Inayah; Saparuddin Siregar; Sugianto Sugianto; Isnaini Harahap; Nurlaila Nurlaila; Muslim Marpaung (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2026)
This study examines the relationship between Islamic profit-sharing rates and conventional bank interest rates within Indonesia’s dual banking system. Using a Vector Autoregression (VAR) model with monthly data from January 2017 to December 2023 (N = 84), the study analyzes the dynamic interactions between banking variables and macroeconomic indicators. The results show that Islamic profit-sharing rates are not significantly affected by conventional interest rates, indicating relative independence from the conventional banking system. Instead, Islamic deposit returns respond significantly to macroeconomic factors, particularly inflation and GDP. Impulse response analysis confirms that shocks to inflation and GDP have a stronger impact on Islamic profit-sharing rates than shocks from conventional banking variables. Granger causality results further reveal that conventional interest rates do not predict Islamic profit-sharing rates, while Islamic deposit returns significantly influence GDP and the exchange rate. These findings suggest that Islamic banking follows a distinct transmission mechanism driven primarily by macroeconomic fundamentals rather than conventional interest rate movements. This study contributes to the Islamic finance literature by providing empirical evidence on the relative autonomy of Islamic banking within a dual banking system.